Exploring the potential of bromelain in orthodontic treatment - Estuningtyas, Maria Felicitas Ajeng; Karunia, Dyah; Retnaningrum, Yanuarti (Majalah Kedokteran Gigi Indonesia, 2025)
Bromelain, a proteolytic enzyme derived from pineapple, has attracted significant attention in both medicine and dentistry due to its diverse therapeutic properties. It has been widely studied for its anti-inflammatory, digestive, and wound-healing effects. In dentistry, bromelain has been investigated for applications such as reducing postoperative pain, facilitating enamel deproteinization, aiding in caries removal, and serving as an endodontic irrigant. In orthodontics, its potential lies in deproteinizing enamel to improve the bond strength of orthodontic brackets during placement. Studies suggest that applying bromelain prior to acid etching can enhance bracket bond strength, providing a safer and more efficient alternative to sodium hypochlorite. It has also shown promise in reducing plaque accumulation and gingivitis, particularly in patients with fixed orthodontic appliances. Bromelain’s antibacterial and anti-inflammatory properties support its role in maintaining oral hygiene and promoting healing. However, most existing evidence comes from in vitro or short-term clinical studies. Long-term clinical trials are needed to confirm its safety and efficacy in routine orthodontic practice.